2022
DOI: 10.1111/1750-3841.16208
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–ZnO nanocomposite coating for inhibition of Listeria monocytogenes on the surface and within white brined cheese

Abstract: Several types of cheeses including white brined cheese have been linked to listeriosis outbreaks worldwide. This study aimed to (i) investigate the in vitro inhibitory activity of zinc oxide (ZnO) nanoparticles (NPs) at concentrations of 0.0125-0.1% against three Listeria monocytogenes strains at 10 or 37 • C, (ii) evaluate the antimicrobial efficiency of chitosan-based coating containing 1.0% ZnO NPs against L. monocytogenes on the surface or inside vacuum-packaged white brined cheese at 4 or 10 • C, and iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Several phytochemicals with antimicrobial properties have been reported to be present in E. purpurea extract with proven antimicrobial activity against microbes such as Mycobacterium smegmatis, Streptococcus pyogenes, E. coli, Bacillus subtilis, Staphylococcus aureus , Pseudomonas aeruginosa, and Enterococcus faecalis [12] . Several studies, such as Pluta-Kubica et al [40] , Olaimat et al [41] and Chen et al [42] , have reported a significant decrease in spoilage and pathogenic microbial counts during storage for the food samples, such as cheese, packaged within the edible films containing nanoparticles as bioactive agents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Several phytochemicals with antimicrobial properties have been reported to be present in E. purpurea extract with proven antimicrobial activity against microbes such as Mycobacterium smegmatis, Streptococcus pyogenes, E. coli, Bacillus subtilis, Staphylococcus aureus , Pseudomonas aeruginosa, and Enterococcus faecalis [12] . Several studies, such as Pluta-Kubica et al [40] , Olaimat et al [41] and Chen et al [42] , have reported a significant decrease in spoilage and pathogenic microbial counts during storage for the food samples, such as cheese, packaged within the edible films containing nanoparticles as bioactive agents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Migration is a diffusion process wherein NPs move from the package into the product (de Oliveira et al., 2019; Nikolic et al., 2021). It is necessary to pay attention to the safety and migration properties of CHNPs, especially when the CHNPs contain metals or other compounds that may pose toxic effects (Olaimat et al., 2022; Parida et al., 2022; Zhang & Rhim, 2022). The European Commission has standardized some analytical methods to examine the migration of NPs‐containing films (Zhang & Rhim, 2022), and has indicated that the migration rates must be under 1000 μg/dm 2 or 60 mg/kg food (Gasti et al., 2022).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…in complex matrixes [ 13 , 14 ]. But similar studies targeting L. monocytogenes are scarce as most combine the CN with metal ions, essential oils, or other compounds [ 15 , 16 , 17 , 18 ], and in most cases, these types of studies are applied for pure cultures [ 19 ]. Furthermore, great variation has been observed in the antimicrobial properties reported for CM/CN by different research groups.…”
Section: Introductionmentioning
confidence: 99%